Partisipasi petani pada penerapan teknik rehabilitasi lahan dan konservasi tanah di wilayah DAS mikro - M. Kudeng Sallata (Foresty Faculty of Hasanuddin University, 2016)
This study aims to determine the level of farmers participation in the implementation of land rehabilitation and soil conservation (LRSC) techniques where appropriate to the micro watershed through PRA and PAR approaches. The techniques of LRSC both mechanical and vegetative methods have been built in a participatory manner in the demonstration plots of 2 ha in Datara micro watershed and of 2.5 ha in Mararin also micro watershed, South Sulawesi. Gully plug equipped with stick-scale and V-notch weir were constructed in Datara micro watershed and concrete tank of mud and runoff was built in Mararin micro watershed to monitor the impact of LRSC actvities to sedimentation and runoff level. The results showed the level of farmers participation at both locations fluctuated in the category of low (<50%), moderate (50-79%) and high (>80%) against targets LRSC activities that have been agreed at a meeting of the group. The level of participation is determined from the condition of the microhydro electric power who have built together. Participation of farmers on the application of LRSC on both plots are: willing to lend of their land for the location of demonstration plots, planting and maintaining trees for timber production, building and maintaining contour terraces and channel of water drainages, maintaining grass and gliricidia as reinforcement terraces for soil conservation techniques. Activities of LRSC impact plots show that layers of sedimentation and runoff volume decreased in the research sites. Demonstration plots in Datara, high sedimentation layer in the second year (2011) in gully plug average of 32.72 cm decline to 7.14 cm in the fourth year (2013), as well as runoff discharge 44.47 liter/sec in 2010 down to 22.8 liter/sec in November 2013. in Mararin plots the average height of a layer of mud in the tank in 2011 from 4.89 cm decline to 1.99 cm in November 2013 and the runoff volume 8.5 liter/sec down to 5.6 liter/sec at the same time.